Properties of Medium Density Fibreboard Manufactured from Extracted and Unextracted Acacia Catechu Wood Chips - Mayuree, Doungpet (1990)
The project was carried out to evaluate the properties of medium density fibreboard from the extracted and unextracted woodchips. The boards were produced with a 13 % urea resin, and a 3 % isocyanate resin to obtain three densities which were targetted at 650, 750, and 850 kg/m³. The same resin concentrations and types were used to produce board of the target density of 750 kg/m³. The properties of the boards from the extracted unextracted materials were determined and compared. and The chemical components of the wood were 64.27 % holocellulose, 35.63 % alhpa-cellulose, 34.38 % lignin and 1.5 % ash, with the pH of 5 to 5.1. The extracted woodchips yielded 88.35 % fibre whilst the unextracted woodchip yielded 77.92 % fibre. The strength properties of boards from the extracted woodchip with 13 % urea resin met the 300-type of JISA 5906 for all three densities . The boards with 3 % isocyanate resin met the 150-type for 650 kg/m3 and 750 kg/m3 and met the 300-type for 850 kg/m³. The urea bonded boards gave higher strength than those bonded by isocyanate resin. The 750 kg/m³ boards from the unextracted woodchip gave higher MOR with the urea than the isocyanate resin